Systematic and intestinal antibody-secreting cell responses and correlates of protective immunity to human rotavirus in a gnotobiotic pig model of disease. - Yuan, L (1996)
Neonatal gnotobiotic pigs orally inoculated with virulent (intestinal-suspension) Wa strain human rotavirus (which mimics human natural infection) developed diarrhea, and most pigs which recovered (87% protection rate) were immune to disease upon homologous virulent virus challenge at postinoculation day (PID) 21. Pigs inoculated with cell culture-attenuated Wa rotavirus (which mimics live oral vaccines) developed subclinical infections and seroconverted but were only partially protected against challenge (33% protection rate). Isotype-specific antibody-secreting cells (ASC were enumerated at selected PID in intestinal (duodenal and ileal lamina propria and mesenteric lymph node [MLN]) and systemic (spleen and blood) lymphoid tissues by using enzyme-linked immunospot assays. At challenge (PID 21), the numbers of virus-specific immunoglobulin A (IgA) ASC, but not IgG ASC, in intestines and blood were significantly greater in virulent-Wa rotavirus-inoculated pigs than in attenuated-Wa rotavirus-inoculated pigs and were correlated (correlation coefficients: for duodenum and ileum, 0.9; for MLN, 0.8; for blood, 0.6) with the degree of protection induced. After challenge, the numbers of IgA and IgG virus-specific ASC and serum-neutralizing antibodies increased significantly in the attenuated-Wa rotavirus-inoculated pigs but not in the virulent-Wa rotavirus-inoculated pigs (except in the spleen and except for IgA ASC in the duodenum). The transient appearance of IgA ASC in the blood mirrored the IgA ASC responses in the gut, albeit at a lower level, suggesting that IgA ASC in the blood of humans could serve as an indicator for IgA ASC responses in the intestine after rotavirus infection. To our knowledge, this is the first report to study and identify intestinal IgA ASC as a correlate of protective active immunity in an animal model of human-rotavirus-induced disease.